2021
DOI: 10.3389/fpsyg.2021.800515
|View full text |Cite
|
Sign up to set email alerts
|

Gender Difference in the Relationship of Physical Activity and Subjective Happiness Among Chinese University Students

Abstract: Background: Gender makes a difference in health and physical activity (PA). This research aimed to identify the gender difference in the relationship of PA and subjective happiness among Chinese university students.Methods: A cross-sectional survey was conducted in Shanghai Jiao Tong University from July 7 to 17 in 2021, using an anonymous online self-report questionnaire. The questionnaire included the Chinese version of the International Physical Activity Questionnaire-Short Form (IPAQ-SF), the Subjective Ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 42 publications
0
14
0
Order By: Relevance
“…Of these, three articles were studied at Beijing universities [ 10 , 11 , 12 ], two at Shanghai universities [ 12 , 13 ], two at Guangdong universities [ 14 , 15 ], one at Shandong universities [ 16 ], one at Anhui universities [ 17 ], one at Hubei universities [ 18 ], one at Henan universities [ 19 ], one at Guangxi universities [ 20 ], and one at Guizhou universities [ 21 ], while the rest did not clearly show the name of the university or the area in which the university is located [ 22 , 23 , 24 ]. Two eastern universities, two southern universities, four northern universities, and four central universities remained unspecified.…”
Section: Resultsmentioning
confidence: 99%
“…Of these, three articles were studied at Beijing universities [ 10 , 11 , 12 ], two at Shanghai universities [ 12 , 13 ], two at Guangdong universities [ 14 , 15 ], one at Shandong universities [ 16 ], one at Anhui universities [ 17 ], one at Hubei universities [ 18 ], one at Henan universities [ 19 ], one at Guangxi universities [ 20 ], and one at Guizhou universities [ 21 ], while the rest did not clearly show the name of the university or the area in which the university is located [ 22 , 23 , 24 ]. Two eastern universities, two southern universities, four northern universities, and four central universities remained unspecified.…”
Section: Resultsmentioning
confidence: 99%
“…Especially for young people, physical exercise and internet use have become an essential part of a modern lifestyle, contributing not only to physical and mental health but also to the health of society [ 4 ]. Existing studies have found that physical exercise and internet use impact subjective well-being [ 5 , 6 ]. At the same time, compared with other age groups, youth groups participate in physical exercise and use the internet more frequently [ 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Third, this paper systematically examines the heterogeneity of benefits brought by physical activity. Literature demonstrates variations in exercise habits among people with different characteristics (31)(32)(33)(34)(35)(36)(37)(38)(39), but it is unclear whether there also exist heterogeneities in the health benefits of physical activity. Based on this, this paper systematically examines whether physical exercise brings health benefits to people with depressive disorders using a large-scale representative micro dataset in China, and conducts mechanism analysis from the perspective of multidimensional subjective wellbeing.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, women exhibit higher levels of depression and therefore are more likely to gain health benefits from regular exercises ( 17 , 32 ). Compared to men's preference for vigorous exercise, women are more likely to engage in low-intensity activities, such as walking, jogging and yoga ( 36 ). For example, square dancing, which is widely practiced among older people in China, can effectively reduce mental disorders ( 37 ).…”
Section: Introductionmentioning
confidence: 99%